RĀ’ DALAM YESAYA 45:7 ANALISIS LEKSIKAL DAN IMPLIKASI BAGI TEOLOGI KEDAULATAN ILAHI - Febi Febriyanti; Tridio Patiku; Rein Patoding (ADISAM PUBLISHER, 2026)
This article aims to lexically analyze the term rā’ in Isaiah 45:7 and examine its implications for the theology of divine sovereignty. The main problem studied is how to understand the use of the word rā’, which in some translations is often equated with “evil,” thus raising theological questions about God’s relationship with evil. This research uses a qualitative approach through analysis of the Hebrew text, a study of the historical context of Deutero-Isaiah, and dialogue with Indonesian Old Testament theological literature. The results of the study show that lexically rā’ has a broad spectrum of meanings and in the context of Isaiah 45:7 is more appropriately understood as a historical calamity or tribulation, rather than a moral evil. The parallelism structure of Hebrew poetry and the background of the Babylonian exile reinforce this meaning as part of the affirmation of monotheism and God’s sovereignty over history. The theological implications emphasize that divine sovereignty encompasses all of reality without making God the source of sin.